Conflict, Rockets, and Birth Outcomes: Evidence from Israel's Operation Protective Edge - Shirlee Lichtman-Sadot; Neta Benshalom-Tirosh; Eyal Sheiner (Institute of Labor Economics (IZA), 2020)
In summer 2014, southern Israel experienced rocket attacks from the Hamas-ruled Gaza strip on a nearly daily basis for over 50 consecutive days. We exploit this unexpected escalation in the Israeli-Palestinian conflict and variation across localities in Israel in the amount of sirens that warned of rocket attacks to measure the effect of conflict intensity on birth weight and gestation length among mothers who were pregnant during this period. In addition to the common notion that conflict intensity induces stress and anxiety, we also show that conflict intensity is correlated with absences from work and lack of prenatal care. Results on changes in birth outcomes are consistent with a detrimental effect of stress and reduced prenatal care and a beneficial effect of reduced work attendance during pregnancy. Our results demonstrate that multiple factors can impact birth outcomes when evaluating the effect of armed conflict and that the effects can also be qualitatively different.
Keywords: I10; I12; 330; birth outcomes; prenatal stress; prenatal care; Israeli-Palestinian conflict